The Implementation of the Ummi Method in Memorizing Short Qur’anic Surahs at Khalifah 27 Kindergarten Jakabaring Palembang - Satia Utami; Ali Murtopo; Elsa Cindrya (AlBanna: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aimed to describe the implementation of the Ummi Method in improving the ability to memorize short surahs at TK Khalifah 27 Jakabaring Palembang. The study was motivated by the varying abilities of young children in memorizing short surahs, indicating the need for a learning method that is appropriate to their developmental characteristics. This research employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving the principal, classroom teacher, Ummi Method teacher, and students. The data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through triangulation. The findings revealed that the implementation of the Ummi Method was carried out systematically through opening activities, muraja’ah (memorization review), classical and individual learning, and repeated memorization using the one-verse-per-day system. The method helped children memorize short surahs gradually, improved the fluency and accuracy of recitation, and increased their confidence in presenting their memorization. The successful implementation of the Ummi Method was supported by teachers’ competence, appropriate learning media, and collaboration between the school and parents in guiding children’s muraja’ah at home. Therefore, the implementation of the Ummi Method effectively supports the development of young children's ability to memorize short surahs at TK Khalifah 27 Jakabaring Palembang. [Penelitian ini bertujuan untuk mendeskripsikan implementasi penerapan Metode Ummi terhadap kemampuan menghafal surah pendek di TK Khalifah 27 Jakabaring Palembang. Penelitian ini dilatar belakangi oleh masih beragamnya kemampuan anak dalam menghafal surah pendek sehingga diperlukan metode pembelajaran yang sesuai dengan karakteristik anak usia dini. Penelitian menggunakan pendekatan kualitatif dengan jenis penelitian deskriptif. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi terhadap kepala sekolah, guru kelas, dan peserta didik. Data dianalisis melalui reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan keabsahan data diuji menggunakan triangulasi. Hasil penelitian menunjukkan bahwa implementasi Metode Ummi telah dilaksanakan secara sistematis melalui kegiatan pembukaan, muroja’ah, pembelajaran klasikal dan individual, serta pengulangan hafalan dengan sistem satu hari satu ayat. Penerapan metode ini membantu anak menghafal surah pendek secara bertahap, meningkatkan kelancaran hafalan, ketepatan pelafalan, dan kepercayaan diri dalam menyetorkan hafalan. Keberhasilan implementasi Metode Ummi didukung oleh kompetensi guru, penggunaan media pembelajaran yang sesuai, serta kerja sama antara sekolah dan orang tua dalam membimbing muroja'ah di rumah. Dengan demikian, penerapan Metode Ummi mampu mendukung perkembangan kemampuan menghafal surah pendek pada anak usia dini di TK Khalifah 27 Jakabaring Palembang.]